Cement-based friction nanogenerator and preparation method and application thereof
Patent Information
- Application Number
- CN202510504057.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]当前主流聚合物基摩擦纳米发电机已实现高功率密度,但材料成本较为高昂,流程繁琐且材料的机械性能不足等缺陷严重制约了规模化应用
[0039]有益效果:和现有技术相比,本发明具有如下显著性特点:本发明利用水泥基材料制作摩擦纳米发电机,其成本低廉,结构简单,易于大规模制造以及推广应用,且机械性能较聚合物基摩擦纳米发电机更高,服役寿命更长。本发明所制备的水泥基摩擦纳米发电机在不同室内外、压力、湿度环境下皆可保持良好的输出性能。本发明能够将机械能有效的转换为电能,有效实现了摩擦纳米发电机与水泥基材料的无缝集成,特别的它能够收集分布广泛、频率低、分布无规则的机械能转换为电能,为小型电力设备、自供电建筑监测传感器等提供电力支持,为新型绿色基础设施提供技术支撑。
Smart Images

Figure CN122969408A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mechanical energy harvesting technology, specifically relating to a high-energy-conversion cement-based triboelectric nanogenerator, its preparation method, and its application. Background Technology
[0002] The competitive landscape of the energy industry is undergoing profound changes, with increasingly fierce competition between clean and traditional energy sources. As support for new energy sources diminishes, constructing a new, sustainable energy conversion system has become a core issue urgently needing resolution. In the future, energy will continue to drive a green and low-carbon transformation, converting vast amounts of environmental energy into electricity to meet the ongoing demand for cleaner and more sustainable energy – a major challenge for researchers. Our living environment is rich in mechanical energy, including human movement, vehicle motion, and any form of vibration. Triboelectric nanogenerators offer a self-powered and feasible solution for converting mechanical energy into electricity, potentially meeting the growing energy demands of the upcoming green and low-carbon transition.
[0003] While current mainstream polymer-based triboelectric nanogenerators have achieved high power density, their large-scale application is severely hampered by high material costs, cumbersome processes, and insufficient mechanical properties. Chinese patent CN119298710A discloses a method for preparing a high-humidity-resistant wood-based triboelectric nanogenerator. To ensure the triboelectric polarity of the wood, it requires modification treatments such as chemical treatment, plasma etching, and hot pressing. This process is complex and may result in insufficient mechanical strength of the material itself, leading to impaired output performance or reduced durability. Chinese patent CN119675490A provides a highly efficient spherical non-contact triboelectric nanogenerator for collecting low-frequency wave energy. It consists of an outer spherical shell, an inner spherical shell, a oscillating component, bearings, a shaft, a counterweight, and triboelectric power generation units. This process is complex and costly.
[0004] Cement is a major component of infrastructure exposed to mechanical energy, such as buildings, roads, and sidewalks. As a widely used building material, cement has higher mechanical strength and lower cost compared to commonly used polymer-based triboelectric nanogenerators. It is also easy to combine with other materials for targeted performance optimization. Therefore, the research and optimization of cement-based triboelectric nanogenerators is highly feasible, and further research in this field is necessary. This may provide new perspectives for energy transition, low-carbon infrastructure, and the development of smart cities.
[0005] Traditional cement-based materials have poor polarity. As triboelectric materials, the low dielectric constant of cement, the porous microstructure between hydration products, and the single-point contact between spherical cement particles all greatly reduce the charge transport rate, resulting in low output performance of cement-based triboelectric nanogenerators. Therefore, how to modify cement to improve the affinity between cement hydration products and electrons, and optimize the conduction barriers for effective transfer and collection of triboelectric charges, so as to obtain inexpensive, low-carbon and environmentally friendly cement-based triboelectric nanogenerators, still faces great challenges. Summary of the Invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a cement-based triboelectric nanogenerator with high energy conversion and high mechanical properties.
[0007] The technical problem that this invention also aims to solve is to provide a method for preparing a low-cost, low-carbon, and environmentally friendly cement-based triboelectric nanogenerator.
[0008] The final technical problem to be solved by this invention is to provide an application of cement-based triboelectric nanogenerators.
[0009] Technical Solution: To solve the above-mentioned technical problems, the present invention provides a cement-based triboelectric nanogenerator, which includes a positive friction layer and a negative friction layer. The positive friction layer includes a modified cement-based material and a positive electrode material cast in the modified cement-based material. The negative friction layer includes a negative electrode material and a negative friction material loaded on the negative electrode material. The modified cement-based material is prepared by modifying cement with dopamine hydrochloride, polyethyleneimine and polyacrylonitrile.
[0010] The negative friction material is 0.5-1 mm thick polytetrafluoroethylene or silicone rubber.
[0011] The cement type is P·Ⅰ42.5, P·O 42.5 or P·O 52.5.
[0012] The modified cement-based material is made from the following raw materials in parts by weight: 45-100 parts cement, 0.5-3 parts water-reducing agent, 0.8-1.2 parts polyacrylonitrile, and 18-40 parts a mixture of dopamine hydrochloride modified solution and polyethyleneimine solution. The dopamine hydrochloride modified solution is obtained by mixing dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution, and the polyethyleneimine solution is obtained by mixing polyethyleneimine with deionized water.
[0013] The present invention also includes a method for preparing the cement-based triboelectric nanogenerator, comprising the following steps:
[0014] 1) Preparation of modified cement-based materials: A mixture of dopamine hydrochloride modified solution and polyethyleneimine solution, cement, water-reducing agent and polyacrylonitrile powder are mixed and stirred until all components are uniformly mixed to obtain a mixture. The dopamine hydrochloride modified solution is obtained by mixing dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution, and the polyethyleneimine solution is obtained by mixing polyethyleneimine with deionized water.
[0015] 2) Preparation of positive friction layer: The mixture is poured, an electrode mesh is placed in the middle layer of the poured specimen, and the positive friction layer is obtained after curing.
[0016] 3) Preparation of cement-based triboelectric nanogenerator: A negative friction material is loaded onto a negative electrode material to obtain a negative friction layer, and the positive and negative friction layers are assembled to obtain a cement-based triboelectric nanogenerator.
[0017] In step 1), the volume ratio of the dopamine hydrochloride modified solution to the polyethyleneimine solution is 2:1 to 3, and the mass ratio of the dopamine hydrochloride to the tris(hydroxymethyl)aminomethane buffer solution is 1:3000 to 10000.
[0018] The concentration of the polyethyleneimine solution in step 1) is 1–3 mg / ml.
[0019] In step 1), the water-reducing agent is a polycarboxylate water-reducing agent, the dosage of which is 0.5-3% of the cement mass, and the polyacrylonitrile is 0.8-1.2% of the cement mass.
[0020] In step 2), the electrode mesh is a 30-60 mesh copper mesh, and in step 3), the negative electrode material is a copper patch.
[0021] The present invention also includes the application of the cement-based triboelectric nanogenerator in energy transition or low-carbon infrastructure.
[0022] The method for preparing a cement-based triboelectric nanogenerator according to the present invention specifically includes the following steps:
[0023] Step 1: Mix dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer to prepare a pre-reaction solution; mix polyethyleneimine with deionized water to obtain a polyethyleneimine solution;
[0024] Step 2: Mix the dopamine hydrochloride modified solution and the polyethyleneimine solution, and disperse them by ultrasonication to obtain a mixture;
[0025] Step 3: Mix the mixture with cement, water-reducing agent, and polyacrylonitrile powder, then pour it into the casting. Place the electrode mesh in the middle layer of the casting specimen.
[0026] Step 4: After the specimens obtained in Step 4 have been cured, the structure is assembled using 0.5-1 mm thick polytetrafluoroethylene or silicone rubber as the negative friction material and copper foil as the negative friction electrode to obtain a cement-based triboelectric nanogenerator.
[0027] Furthermore, in step one, the mass ratio of dopamine hydrochloride to tris(hydroxymethyl)aminomethane buffer is 1:500;
[0028] Further, in step one, the concentration of the tris(hydroxymethyl)aminomethane buffer solution is 50-100 mM, the pH is 7-9.5, and the concentration of the polyethyleneimine dispersion is 1-3 mg / ml;
[0029] Furthermore, in step one, the volume ratio of the dopamine hydrochloride modified solution to the polyethyleneimine solution is 0.5 to 4.
[0030] Furthermore, in step one, the cement type is P·O 42.5, the water-reducing agent type is polycarboxylate water-reducing agent (solid content is 35-40%), and the water-reducing agent dosage is 1% of the cement mass;
[0031] Further, in step one, the water-cement ratio of the concrete is 0.35 to 0.5, preferably 0.4 to 0.5, the polyacrylonitrile is 1.2% of the cement mass, and the electrode mesh is a 60-mesh copper mesh or copper sheet;
[0032] Further, in step one, the concrete preparation method is to stir cement, water-reducing agent, and polyacrylonitrile powder for 1 minute, add modified precast solution and stir for 2-3 minutes until all components are mixed evenly, pour the mixture into a mold and vibrate for 15 seconds.
[0033] The high-energy-conversion cement-based triboelectric nanogenerator of this invention operates in four steps:
[0034] 1) In the initial stage (state I), when the cement-based material is in contact with the negative friction layer as a positive friction layer, due to the contact electrification effect, electrons are transferred from the cement surface to the surface of the negative friction layer, forming different surface charges on the surfaces of the two friction layer materials and accumulating continuously until saturation.
[0035] 2) When the surfaces of the two friction layers separate due to mechanical force (state II), the potential on the surfaces of the two friction layer materials decreases with the relative displacement. In order to balance the potential difference caused by the friction charge, electrons on the negative friction layer are transferred to the positive friction layer through the electrode to fill the hole, and a positive current signal is generated.
[0036] 3) When the two surfaces move away from each other (state III), electron transfer stops. When the two friction layers approach each other again, the potential difference will continue to drive the transfer of electrons between the two electrodes in the external circuit.
[0037] 4) The two friction layers close again (state IV), the potential difference between the two friction layers disappears, and electrons flow back to the original electrode.
[0038] Mechanism of the invention: The present invention modifies cement by combining dopamine hydrochloride and polyethyleneimine and doping it with polyacrylonitrile, thereby loading the cement surface with abundant amino, hydroxyl and cyano groups, which can significantly enhance the positive triboelectric polarity of the cement, thereby increasing the output performance of cement-based triboelectric generators.
[0039] Beneficial Effects: Compared with existing technologies, this invention has the following significant advantages: This invention utilizes cement-based materials to fabricate triboelectric nanogenerators, which are low-cost, simple in structure, easy to mass-produce and widely apply, and exhibit higher mechanical properties and longer service life than polymer-based triboelectric nanogenerators. The cement-based triboelectric nanogenerator prepared by this invention maintains good output performance under various indoor and outdoor, pressure, and humidity environments. This invention can effectively convert mechanical energy into electrical energy, achieving seamless integration of triboelectric nanogenerators and cement-based materials. In particular, it can collect widely distributed, low-frequency, and irregularly distributed mechanical energy and convert it into electrical energy, providing power support for small-scale power equipment, self-powered building monitoring sensors, etc., and providing technical support for new green infrastructure. Attached Figure Description
[0040] Figure 1 This is a schematic diagram of the structure of the cement-based triboelectric nanogenerator of the present invention;
[0041] Figure 2 This is a schematic diagram illustrating the working principle of the cement-based triboelectric nanogenerator of the present invention;
[0042] Figure 3 These are SEM images of the dopamine hydrochloride and polyethyleneimine-modified cement prepared according to this invention.
[0043] Figure 4 This is a nitrogen element distribution diagram of the dopamine hydrochloride and polyethyleneimine modified cement prepared by this invention;
[0044] Figure 5 The output voltage performance of cement-based triboelectric nanogenerators with different PEI dosages prepared in this invention is shown in the figure; in the figure, PDA:PEI-0, 2:1, 2:1.5, 2:2, 2:2.5, and 2:3 represent the concentration ratio of polydopamine to polyethyleneimine.
[0045] Figure 6 The output current performance of cement-based triboelectric nanogenerators with different PEI doping contents prepared in this invention is shown in the figure.
[0046] Figure 7The output voltage performance of cement-based triboelectric nanogenerators with different PAN content prepared in this invention is shown in the figure; PAN-0, 0.4, 0.6, 0.8, 1, 1.2 in the figure represent the mass percentage concentration of polyacrylonitrile in cement as 0, 0.4, 0.6, 0.8, 1.0, and 1.2%, respectively.
[0047] Figure 8 The output current performance of cement-based triboelectric nanogenerators with different PAN content prepared according to this invention is shown in the figure.
[0048] Figure 9 This refers to the compressive strength of the cement-based triboelectric nanogenerator prepared by the inventors. The horizontal axis in the figure represents the concentration of polyethyleneimine at 0, 1, 1.5, 2, 2.5, and 3 mg / ml.
[0049] Figure 10 This is a rendering of the cement-based triboelectric nanogenerator prepared according to the present invention illuminating a commercial LED. Detailed Implementation
[0050] Unless otherwise specified, all materials, reagents, and instruments used in the following examples are commercially available. Experimental methods not specifically described in the examples are generally performed under standard conditions or as recommended by the manufacturer.
[0051] Dopamine Hydrochloride: Shanghai Aladdin Biotechnology Co., Ltd.: Model: D103111
[0052] Tris(hydroxymethyl)aminomethane: Shandong Keyuan Biochemical Co., Ltd.: Model: T823912
[0053] Polyethyleneimine: Shanghai Maclean Biochemical Technology Co., Ltd.: Model: E808878
[0054] Polycarboxylate superplasticizer: Shanghai Chenqi Chemical Technology Co., Ltd., Product No.: 540P.
[0055] Example 1
[0056] A method for preparing a high-energy-conversion cement-based triboelectric nanogenerator includes the following steps:
[0057] (1) Mix dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution. The concentration of tris(hydroxymethyl)aminomethane buffer solution is 50 mM and pH 8.5. Weigh 0.08 g of dopamine hydrochloride and 20 g of tris(hydroxymethyl)aminomethane buffer solution to prepare a dopamine pre-reaction solution. Weigh 0.08 g of polyethyleneimine and 20 g of deionized water to prepare a polyethyleneimine solution. Mix the dopamine pre-reaction solution and the polyethyleneimine solution to obtain a mixture of dopamine hydrochloride and polyethyleneimine with a final concentration of 2 mg / ml.
[0058] (2) Disperse the mixture by ultrasonication for 10 min at an ultrasonic frequency of 20 kHz and an ultrasonic power of 60 W. Stir on a magnetic stirring table for 24 h until it turns brown, and finally obtain the modified solution.
[0059] (3) Weigh 100g of cement, 1g of water-reducing agent and 1g of polyacrylonitrile powder and put them into a mixing pot. Stir at 200 rpm for 1 min to make the powder evenly mixed. Then add 40g of modified solution into the mixing pot and stir at 300 rpm for 2 min until the slurry has good workability.
[0060] (4) Pour the mixed mixture into a mold, insert a 60-mesh copper mesh electrode into the center of the specimen before the modified cement sets, and place the specimen in a standard curing box for 28 days.
[0061] (5) Using 0.5 mm polytetrafluoroethylene as the negative friction layer and copper patch as the negative electrode, the positive and negative friction electrodes are assembled to obtain a cement-based triboelectric nanogenerator.
[0062] In this embodiment, the concentration of polyethyleneimine is 2 mg / ml, and the negative friction layer material is a polytetrafluoroethylene film, which has a good difference in electronegativity compared with the modified cement-based material.
[0063] In subsequent examples, we fixed the concentration of dopamine hydrochloride at 2 mg / ml and adjusted the concentration of polyethyleneimine.
[0064] Example 2
[0065] A method for preparing a high-energy-conversion cement-based triboelectric nanogenerator includes the following steps:
[0066] (1) Mix dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution. The concentration of tris(hydroxymethyl)aminomethane buffer solution is 50 mM and pH 8.5. Weigh 0.04 g of dopamine hydrochloride and 10 g of tris(hydroxymethyl)aminomethane buffer solution to prepare a dopamine pre-reaction solution. Weigh 0.02 g of polyethyleneimine and 10 g of deionized water to prepare a polyethyleneimine solution. Mix the dopamine pre-reaction solution with the polyethyleneimine solution to obtain a mixture with a dopamine hydrochloride concentration of 2 mg / ml and a polyethyleneimine concentration of 1 mg / ml.
[0067] (2) Disperse the mixture by ultrasonication for 10 min at an ultrasonic frequency of 20 kHz and an ultrasonic power of 60 W. Stir on a magnetic stirring table for 24 h until it turns brown, and finally obtain the modified solution.
[0068] (3) Weigh 80g of cement, 0.8g of water-reducing agent and 0.8g of polyacrylonitrile powder and place them in a mixing pot. Stir at 200 rpm for 1 min to make the powder evenly mixed. Then add 20g of modified solution to the mixing pot and stir at 300 rpm for 2 min until the slurry has good workability.
[0069] (4) Pour the mixed mixture into a mold, insert a 60-mesh copper mesh electrode into the center of the specimen before the modified cement sets, and place the specimen in a standard curing box for 28 days.
[0070] (5) Using 0.5 mm polytetrafluoroethylene as the negative friction layer and copper patch as the negative electrode, the positive and negative friction electrodes are assembled to obtain a cement-based triboelectric nanogenerator.
[0071] Example 3
[0072] A method for preparing a high-energy-conversion cement-based triboelectric nanogenerator includes the following steps:
[0073] (1) Mix dopamine hydrochloride with 50mM pH 8.5 tris(hydroxymethyl)aminomethane buffer, weigh 0.036g dopamine hydrochloride and 9g tris(hydroxymethyl)aminomethane buffer to prepare dopamine pre-reaction solution, weigh 0.036g polyethyleneimine and 9g deionized water to prepare polyethyleneimine solution, mix dopamine pre-reaction solution and polyethyleneimine solution to obtain a mixture of dopamine hydrochloride and polyethyleneimine with a final concentration of 2mg / ml.
[0074] (2) Disperse the mixture by ultrasonication for 10 min at an ultrasonic frequency of 20 kHz and an ultrasonic power of 60 W. Stir on a magnetic stirring table for 24 h until it turns brown, and finally obtain the modified solution.
[0075] (3) Weigh 45g of cement, 0.45g of water-reducing agent and 0.45g of polyacrylonitrile powder and place them in a mixing pot. Stir at medium speed for 1 minute to mix the powder evenly. Then add 18g of modified solution to the mixing pot and stir at high speed for 2 minutes until the slurry has good workability.
[0076] (4) Pour the mixed mixture into a mold, insert a 60-mesh copper mesh electrode into the center of the specimen before the modified cement sets, and place the specimen in a standard curing box for 28 days.
[0077] (5) Using 0.5mm silicone rubber as the negative friction layer and copper patch as the negative electrode, the positive and negative friction electrodes are assembled to obtain a cement-based triboelectric nanogenerator.
[0078] In this embodiment, the negative friction layer material is 0.5mm silicone rubber. The output voltage and output current generated by this material and the modified cement-based material are 15V and 0.275μA, respectively. It can be seen that the electronic sequence of the silicone rubber polytetrafluoroethylene is more different from that of the cement-based material, resulting in higher output performance.
[0079] Example 4
[0080] This embodiment is the same as Embodiment 1, except that the final concentration of polyethyleneimine in step 1 is 1.5 mg / ml.
[0081] Example 5
[0082] This embodiment is the same as Embodiment 1, except that the final concentration of polyethyleneimine in step 1 is 2.5 mg / ml.
[0083] Example 6
[0084] This embodiment is the same as Embodiment 1, except that the final concentration of polyethyleneimine in step 1 is 3 mg / ml.
[0085] The voltage output of cement-based triboelectric nanogenerators with different polyethyleneimine content in Examples 1, 2, 4, 5, and 6 was measured using a digital source meter. A cement-based triboelectric nanogenerator prepared using the method of Example 1, but with deionized water instead of the modified solution, was used as a control. Figure 5 and Figure 6 As shown, there are significant differences in the polyethyleneimine concentration between the control group and Examples 1, 2, 4, 5, and 6. Specifically, the output voltage and current of the cement-based triboelectric nanogenerator prepared in the control group were 41 V and 2.09 μA, respectively; the output voltage and current of the cement-based triboelectric nanogenerator prepared in the PDA:PEI-2:1 group were 102.5 V and 3.07 μA, respectively; the output voltage and current of the cement-based triboelectric nanogenerator prepared in the PDA:PEI-2:1.5 group were 110 V and 3.6 μA, respectively; and the output voltage and current of the cement-based triboelectric nanogenerator prepared in the PDA:PEI-2:2 group were 107 V and 3.3 μA, respectively. The cement-based triboelectric nanogenerator prepared in the PEI-2:2.5 group had an output voltage and current of 106 V and 2.8 μA, respectively; the cement-based triboelectric nanogenerator prepared in the PDA:PEI-2:3 group had an output voltage and current of 94.5 V and 3.06 μA, respectively. These results show that the cement-based triboelectric nanogenerator with the PDA:PEI-2:1.5 group (i.e., a polyethyleneimine content of 1.5 mg / ml) exhibited the highest current and voltage output, representing a 248% increase in output voltage compared to ordinary cement. Figure 9As shown, the mechanical property test results indicate that the compressive strength is 54.1 MPa when the polyethyleneimine concentration is 0%, 60.1 MPa when the concentration is 1 mg / ml, 64.2 MPa when the concentration is 1.5 mg / ml, 47.6 MPa when the concentration is 2 mg / ml, 46.2 MPa when the concentration is 2.5 mg / ml, and 45.9 MPa when the concentration is 3 mg / ml. These results show that even the addition of 1.5 mg / ml PEI increases the compressive strength of cement-based materials by 18%.
[0086] Example 7
[0087] This embodiment is identical to Embodiment 1, except that in step three, the mass percentage concentration of polyacrylonitrile powder is 0-1.2% of the cement (specifically including 0, 0.4, 0.6, 0.8, 1.0, and 1.2%). A digital source meter was used to measure the voltage and current output of the cement-based triboelectric nanogenerator with different polyacrylonitrile content in Embodiment 7. Figure 7 and Figure 8 As shown, the cement-based triboelectric nanogenerator prepared with 0% polyacrylonitrile (PAT) content had an output voltage and current of 41 V and 2.09 μA, respectively; the PAT content of 0.4% PAT content resulted in an output voltage and current of 30 V and 1.45 μA, respectively; the PAT content of 0.6% PAT content resulted in an output voltage and current of 35 V and 1.73 μA, respectively; the PAT content of 0.8% PAT content resulted in an output voltage and current of 60 V and 2.96 μA, respectively; the PAT content of 1.0% PAT content resulted in an output voltage and current of 55 V and 2.28 μA, respectively; and the PAT content of 1.2% PAT content resulted in an output voltage and current of 50 V and 2.05 μA, respectively. It can be seen that there are significant differences among the different PAT contents in Example 8. The cement-based triboelectric nanogenerator with a PAT content of 0.8% exhibited the highest current and voltage output.
[0088] Example 8
[0089] To further verify the invention's ability to power small electronic devices, a commercial LED lighting experiment was conducted. For example... Figure 10The image shows the effect of TENG illuminating commercial LEDs. In the power generation system, as the positive and negative friction layer materials come into contact with each other, the cement-based triboelectric nanogenerator described in Example 5 can light up more than 30 LEDs. This result demonstrates the invention's ability to power small electronic devices, and the invention has broad potential for practical applications.
Claims
1. A cement-based triboelectric nanogenerator, characterized in that, The cement-based triboelectric nanogenerator includes a positive friction layer and a negative friction layer. The positive friction layer includes a modified cement-based material and a positive electrode material cast in the modified cement-based material. The negative friction layer includes a negative electrode material and a negative friction material loaded on the negative electrode material. The modified cement-based material is prepared by modifying cement with dopamine hydrochloride, polyethyleneimine, and polyacrylonitrile.
2. The cement-based triboelectric nanogenerator according to claim 1, characterized in that, The negative friction material is 0.5~1 mm of polytetrafluoroethylene or silicone rubber.
3. The cement-based triboelectric nanogenerator according to claim 1, characterized in that, The cement type is P·Ⅰ42.5, P·O 42.5 or P·O 52.
5.
4. The cement-based triboelectric nanogenerator according to claim 1, characterized in that, The modified cement-based material is made from the following raw materials in parts by weight: 45-100 parts cement, 0.5-3 parts water-reducing agent, 0.8-1.2 parts polyacrylonitrile, and 18-40 parts a mixture of dopamine hydrochloride modified solution and polyethyleneimine solution. The dopamine hydrochloride modified solution is obtained by mixing dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution, and the polyethyleneimine solution is obtained by mixing polyethyleneimine with deionized water.
5. The method for preparing the cement-based triboelectric nanogenerator according to any one of claims 1 to 4, characterized in that, Includes the following steps: 1) Preparation of modified cement-based materials: A mixture of dopamine hydrochloride modified solution and polyethyleneimine solution, cement, water-reducing agent and polyacrylonitrile powder are mixed and stirred until all components are uniformly mixed to obtain a mixture. The dopamine hydrochloride modified solution is obtained by mixing dopamine hydrochloride with tris(hydroxymethyl)aminomethane buffer solution, and the polyethyleneimine solution is obtained by mixing polyethyleneimine with deionized water. 2) Preparation of positive friction layer: The mixture is poured, an electrode mesh is placed in the middle layer of the poured specimen, and the positive friction layer is obtained after curing. 3) Preparation of cement-based triboelectric nanogenerator: A negative friction material is loaded onto a negative electrode material to obtain a negative friction layer, and the positive and negative friction layers are assembled to obtain a cement-based triboelectric nanogenerator.
6. The method for preparing a cement-based triboelectric nanogenerator according to claim 5, characterized in that, In step 1), the volume ratio of the dopamine hydrochloride modified solution to the polyethyleneimine solution is 2:1~3, and the mass ratio of the dopamine hydrochloride to the tris(hydroxymethyl)aminomethane buffer solution is 1:3000~10000.
7. The method for preparing a cement-based triboelectric nanogenerator according to claim 5, characterized in that, The concentration of the polyethyleneimine solution mentioned in step 1) is 1~3 mg / ml.
8. The method for preparing a cement-based triboelectric nanogenerator according to claim 5, characterized in that, The water-reducing agent mentioned in step 1) is a polycarboxylate water-reducing agent, and the dosage of the water-reducing agent is 0.5~3% of the cement mass, and the polyacrylonitrile is 0.8~1.2% of the cement mass.
9. The method for preparing a cement-based triboelectric nanogenerator according to claim 5, characterized in that, The electrode mesh mentioned in step 2) is a 30-60 mesh copper mesh, and the negative electrode material mentioned in step 3) is a copper patch.
10. The application of the cement-based triboelectric nanogenerator according to any one of claims 1 to 4 in energy transition or low-carbon infrastructure.
Citation Information
Patent Citations
Preparation method of high-humidity-resistant wood-based friction nano-generator
CN119298710A
Spherical non-contact friction nanometer generator capable of efficiently collecting low-frequency wave energy
CN119675490A